Bioefficacy of Larvicidal and Pupicidal properties of Clerodendrum capitatum and Bridelia machrantha leaves extracts against Malaria Vector, Anopheles gambiae giles [Diptera: Culicidae] - Ileke Kayode David; Adesina Femi Peter (Journal of Biology and Medicine - Peertechz Publications, 2018)
Studies were conducted under ambient condition to assess the bio-efficacy of Clerodendrum capitatum and Bridelia machrantha leaves against developmental stages (larva and pupa) of malaria vector, Anopheles gambiae. One hundred millimeter (100mm) of aqueous solutions of the various plant extracts at various concentrations of 25mg/L, 50mg/L, 100mg/L, 150mg/L and 200mg/L were each put in a labelled transparent bowl. Twenty (20) 3rd/4th larval instar were introduced separately into the C. capitatum and B. machrantha extracts along with a set of control containing rain water without any test solution and all tested concentrations were replicated four times. Similarly, Twenty- two days old pupae of Anopheles mosquito were introduced separately into the various plant extracts. The number of dead larvae and pupae were counted and recorded accordingly after 24 hours of treatment. The results showed that Larvae and pupae mortality of An. gambiae occurred in a dosage-dependent manner. There was no significant differences (p>0.05) in toxicity level of the two plant extracts on An. gambiae larvae at concentrations 25mg/L, 50mg/L, 100mg/L, 150mg/L and 200mg/L. Clerodendrum capitatum at concentrations 25mg/L, 50mg/L, 100mg/L, 150mg/L and 200mg/L caused 30%, 47.5%, 60%, 90% and 100% mortality of An. gambiae larvae after 24 hours of exposure, respectively. Bridelia machrantha extract caused 22.5%, 35%, 50%, 77.5% and 92.5% mortality of An. gambiae larvae after 24 hours of exposure at rates 25mg/L, 50mg/L, 100mg/L, 150mg/L and 200mg/L, respectively. Similar trend of results were recorded on the pupae. C. capitatum had lower LC50 and LC90 recorded when compared to B. machrantha that had the higher value on both larvae and pupae. The use of natural insecticide in the implementation of national policy for the control of malaria vectors should be promoted as they are easily degradable, medicinal and eco-friendly.